Health and literacy: a study of literacy practices in a day hospital in the Western Cape - Harries, Jane (School of Education, 2023)
Located in the Hout Bay Day Hospital, this research project focused on literacy practices as embedded in social context. In exploring how patients - both those regarded as literate arid non literate - engaged with the discourses of medicine as represented by medical texts, symbols and artifacts, their constructions of identity, agency, voice and meaning within the medical domain were examined. It was at the interface between the formal as represented by the medical institution and the informal, represented by individuals from within the community that diverse literacy practices were encountered. While individuals were dependent on the system for medical entitlements and treatment, they were able to rescript dominant medical literacies and technologies within the context of their own health and social needs. What was more important was not patients' encoding and decoding of medical texts but rather how they used their own socially embedded literacies to mediate and gain access to these health care entitlements and medical treatment and the discursive skills and resources that they employed in doing so. Uncovering the processes whereby patients were able to recontextualize their experiences of medical literacy and technologies in the context of their material and social realities was one of the key issues explored in this thesis. The research findings suggested that a discursive boundary existed between patients' conceptions of health and illness and those presented by the medical institution. An understanding of patients' different discursive strategies and their social constructions was developed through ethnographic research methods. A socio-spatial analysis of 'hidden' literacy practices lead me beyond the confines of print literacy (alphabetic literacy and numeracy) and suggested differing ways of 'seeing' and 'reading' literacy, further broadening the concept of literacy to include body or somatic literacy. The manner in which the patient's body was 'read' and narrated as a text on entering the medical space was examined and interpreted. In addition, the way in which patients created their own space from within formal institutional space was discussed. In conclusion I argue that the ways in which local knowledge is constructed by the recipients of health care needs to be explored and examined and that these constructions should be taken into consideration when planning future health care initiatives.